Further delineation of a recognizable type of syndromic short stature caused by biallelic SEMA3A loss‐of‐function variants. Issue 3 (23rd December 2020) - Gileta, Alexander F.; Helgeson, Maria L.; Leonard, Jacqueline M. M.; Pyle, Louise C.; Subramanian, Hari P.; Arndt, Kelly; Hawkes, Colin P.; del Gaudio, Daniela
Abstract: The semaphorin protein family is a diverse set of extracellular signaling proteins that perform fundamental roles in the development and operation of numerous biological systems, notably the nervous, musculoskeletal, cardiovascular, endocrine, and reproductive systems. Recently, recessive loss‐of‐function (LoF) variants in SEMA3A (semaphorin 3A) have been shown to result in a recognizable syndrome characterized by short stature, skeletal abnormalities, congenital heart defects, and variable additional anomalies. Here, we describe the clinical and molecular characterization of a female patient presenting with skeletal dysplasia, hypogonadotropic hypogonadism (HH), and anosmia who harbors a nonsense variant c.1633C>T (p.Arg555*) and a deletion of exons 15, 16, and 17 in SEMA3A in the compound heterozygous state. These variants were identified through next‐generation sequencing analysis of a panel of 26 genes known to be associated with HH/Kallmann syndrome. Our findings further substantiate the notion that biallelic LoF SEMA3A variants cause a syndromic form of short stature and expand the phenotypic spectrum associated with this condition to include features of Kallmann syndrome.